Identification of Campylobacter jejuni, C. coli, C. lari, C. upsaliensis, Arcobacter butzleri, and A. butzleri-Like Species Based on the glyA Gene - Al Rashid, Shahnaz Tahihra (American Society for Microbiology, 2000)
Currently, the detection and identification of Campylobacter and Arcobacter species remains arduous, largely due to cross-species phenotypic similarities and a relatively narrow spectrum of biochemical reactivity. We have developed a PCR-hybridization strategy, wherein degenerate primers are used to amplify glyA fragments from samples, which are then subjected to species-specific oligodeoxyribonucleotide probe hybridizations, to identify and distinguish between Campylobacter jejuni, C. coli, C. lari, C. upsaliensis, Arcobacter butzleri, and an A. butzleri-like species. Evaluation of this strategy with genomic DNA from different type strains suggests that this approach is both specific and sensitive and thus may be applicable in a diagnostic assay to identify and differentiate these highly related species.